The Role of Face to Face Interaction in Indicating Personality - Syamsiah Depalina Siregar; Jasmienti Jasmienti; Pipit Rahayu; Dian Aggraini (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
The aim of this research is to know deeply about the important thing of communication. Their impact has been broadly studied within interactions between humans as well as in the field of human-computer interaction. The emergence of many new information and communication technologies, face-to-face interaction is still widespread and popular. A greater emphasis is put on face-to-face communication which provides greater interaction compared to mass communication. This research included into qualitative research. The results show that communication between students and parents is less than 1 hour and vary often misunderstandings between them. The rejection of the positive aspect of the communication by the students, such as having relaxed communication and having great interest for communication from the parents also leads to the same conclusion. Having some fear in communication with the parents is equally perceived by the different categories of students.